PENGEMBANGAN MEDIA PUZZLE GAMBAR SERI UNTUK KETERAMPILAN MENULIS KARANGAN SEDERHANA BAHASA JERMAN SISWA KELAS XII SMA - ROSATI, MUFIKA (LATERNE, 2016)
In German classes, students need a learning medium, especially in writing. Puzzle picture story is a medium thatcan be used in German learning. Based on NEEDS questionnaire, which were provided in the XII SMAN 13 Surabaya class, there are 55.17% students who have difficulty in writing. And there are 62.07% of students who are interested in learning media. Also a learning medium is needed. The media can help the students to help the writting skills. This study has the formulation of the problem: